Use of hyaluronan (Gengigel) in the treatment of gingivitis in orthodontic patients: A clinical, biochemical, and microbiological study - Palak D Batavia; Kala S Bhushan; K L Vandana; Rajendra Desai (Wolters Kluwer Medknow Publications, 2016)
Introduction: To compare the effects of hyaluronan (Gengigel) alone and in combination with scaling using clinical, microbial, and lactate dehydrogenase (LDH) parameters. Materials and Methods: In this, the three treatment groups included were scaling, scaling plus local application of Gengigel, and Gengigel alone. The 0.2% hyaluronic acid (HA) gel was applied topically and intrasulcularly 0.8% hyaluronan was applied. The clinical parameters, and microbial and biochemical analyses of gingival crevicular fluid (GCF) LDH were assessed. Intragroup comparisons were made by Student's unpaired t-test and intergroup comparisons were done using one-way analysis of variance followed by post hoc Turkey's test. Results: At the end of study period (0-56 day), intergroup comparison demonstrated no significant reduction in plaque index (PI) (0.07 NS), gingival index (GI) (0.99 NS), and LDH (0.70 NS) values. A significant correlation was found between LDH values and bleeding index at all study intervals (0 days, 28 days, and 56 days); gingival index (GI) (0.007 S) was significantly correlated on day 0 and day 56. The microbial reduction was demonstrated. Conclusion: These changes in the clinical, microbial, and biochemical parameters reported with the different treatment modalities clearly support that the use of Gengigel would act as an advantageous adjunct to scaling. Further studies are required to confirm the Gengigel effect using histologic methods.